Pulse interval tunable terahertz radiation from electron beam–plasma interactions - Jian, Die; Cai, Jie; Han, Li-Qi; Zhao, Xing-Yu; Wen, Han; Yu, Jin-Qing (Chinese physics B, 2025)
Terahertz (THz) radiation is rapidly emerging as a powerful tool with diverse applications, including high-speed imaging, laser-driven particle acceleration, and ultra-high frequency (UHF) communications. However, generating multi-pulse THz radiation with controllable time intervals remains a significant challenge. This study presents an approach to overcome this hurdle by exploiting the interaction between an electron beam and plasma. Using numerical simulations and theoretical analysis, we investigated the behavior of an electron beam within a plasma and its interaction with the longitudinal sheath field. This interaction resulted in the generation of multiple distinct THz pulses. We demonstrated that the plasma length adjustment allows for precise tuning of the interval between THz pulses. Moreover, the radiation intensity could be controlled by the electron beam energy and the electron bunch duration. The proposed scheme can generate multi-pulse THz radiation in a flexible and precise manner, paving the way for advancements in applications requiring high temporal resolution.